Battery Thermal Management: An Application to Petrol Hybrid Electric Vehicles - Raja Mazuir Raja Ahsan Shah (17541516) (2023)
Battery thermal management systems (BTMS) in hybrid electric vehicles can be complex and heavy. They tend to increase energy consumption, leading to higher carbon dioxide emissions. In this study, a new approach was investigated for the potential use of four fuel components as coolants for direct liquid-cooled (LC)-BTMS, N-Pentane, N-Hexane, N-Butane, and Cyclo-Pentane. The performance of the fuel components was numerically analysed and CFD modelled using ANSYS Fluent software. Several meshing iterations of the lithium-ion battery (LIB) module were performed to conduct mesh independence check for higher accuracy and less computational time. The LIB module was simulated, in comparison to a free air convection (FAC)-BTMS as a benchmark, at three discharge rates (1C, 1.5C, 2C) for each of the inlet velocity values (0.1, 0.5, 1 m/s). Results show that FAC-BTMS exceeded the LIB module optimal operating temperature range (293–313 K) at 2C. On average, at the worst condition (lowest inlet velocity and highest discharge rate), all fuel components of the LC-BTMS were able to maintain the LIB module temperature below 288 K. That is at least 4.7% cooler compared to FAC-BTMS, which renders the new approach viable alternative to the conventional BTMS. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su15075868